Religious Conflict and Coexistence The Korean Context and Beyond - Lee, Song-Chong; Yoo, Yohan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The articles in this volume present a variety of theoretical and historical cases to enlarge our understanding of religious conflict and coexistence. Seven out of the ten articles discuss cases of major religions in Korea, including Shamanism, Buddhism, Taoism, Confucianism, and Christianity. They explore the particularity of Korean religions in seeking theological and philosophical inclusiveness, playing a positive role in society and building stable interreligious relations. The other three articles cover non-Korean themes including religious conflict of interfaith families, a biblical analysis of particularism and universalism and a new interpretation of Paul's letter to the Romans. All of these articles are aimed at identifying major causes of religious conflict and finding some effective solutions drawn from various theoretical and practical domains.